1991
DOI: 10.1002/hep.1840130209
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal and endosomal heterogeneity in the liver: A comparison of the intracellular pathways of endocytosis in rat liver cells

Abstract: Air-filled albumin microspheres, asialoorosomucoid and formaldehyde-treated serum albumin are selectively taken up by endocytosis in rat liver Kupffer cells, parenchymal cells and endothelial cells, respectively. Intracellular transport and degradation of endocytosed material were studied by subcellular fractionation in sucrose and Nycodenz gradients after intravenous injection of the ligand. By using ligands labeled with 125I-tyramine-cellobiose, the subcellular distribution of labeled degradation products ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The liver endothelial cells also perform an important homeostatic function by removing macromolecules from the circulation, and, recently, increased attention has been paid to these cells (3). Studies of the mechanism of endocytosis and intracellular degradation of fBSA have reported that fBSA is taken up via scavenger receptors on the endothelial cells (10)(11)(12)(13). Using fBSA, we tried to clarify the changes in endocytotic function of sinusoidal cells during liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver endothelial cells also perform an important homeostatic function by removing macromolecules from the circulation, and, recently, increased attention has been paid to these cells (3). Studies of the mechanism of endocytosis and intracellular degradation of fBSA have reported that fBSA is taken up via scavenger receptors on the endothelial cells (10)(11)(12)(13). Using fBSA, we tried to clarify the changes in endocytotic function of sinusoidal cells during liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in receptor-mediated endocytosis in sinusoidal cells during liver regeneration have not been much studied. To elucidate these changes in receptor-mediated endocytosis and to evaluate the functional recovery of sinusoidal cells after partial hepatectomy, we measured receptor-mediated en-docytosis in two-thirds hepatectomized rats using formaldehyde-treated bovine serum albumin, which is endocytosed via scavenger receptors on the sinusoidal cells (10)(11)(12)(13), as an endocytable macromolecule. Receptor-mediated endocytosis in hepatocytes was also measured using asialofetuin, which in mainly taken up by hepatocytes (14,15), and the changes in endocytotic function in sinusoidal cells were compared with that of hepatocytes.…”
mentioning
confidence: 99%